2020
DOI: 10.1016/j.euo.2020.04.006
|View full text |Cite
|
Sign up to set email alerts
|

Rates and Predictors of Perioperative Complications in Cytoreductive Nephrectomy: Analysis of the Registry for Metastatic Renal Cell Carcinoma

Abstract: Background: Cytoreductive nephrectomy (CN) plays an important role in the treatment of a subgroup of metastatic renal cell carcinoma (mRCC) patients. Objective: We aimed to evaluate morbidity associated with this procedure and identify potential predictors thereof to aid patient selection for this procedure and potentially improve patient outcomes. Design, setting, and participants: Data from 736 mRCC patients undergoing CN at 14 institutions were retrospectively recorded in the Registry for Metastatic RCC (RE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 22 publications
0
20
1
1
Order By: Relevance
“…Also, an increased risk of in-hospital mortality (3.6%) for older (≥ 71 years of age) patients was documented, compared to 1.7% and 1.0% in the age groups of 56–70 years and ≤ 55 years, respectively [ 31 ]. Our observed 30-day postoperative mortality was higher than in the recent REMARCC study, which reported 10 (1.3%) deaths and 45 (6.1%) high-grade complications from 736 CNs performed in 14 European institutes [ 32 ]. In our data, it is noteworthy that 6 of the 19 total grade 5 complications did not occur during the first 30-day postoperative period.…”
Section: Discussioncontrasting
confidence: 66%
“…Also, an increased risk of in-hospital mortality (3.6%) for older (≥ 71 years of age) patients was documented, compared to 1.7% and 1.0% in the age groups of 56–70 years and ≤ 55 years, respectively [ 31 ]. Our observed 30-day postoperative mortality was higher than in the recent REMARCC study, which reported 10 (1.3%) deaths and 45 (6.1%) high-grade complications from 736 CNs performed in 14 European institutes [ 32 ]. In our data, it is noteworthy that 6 of the 19 total grade 5 complications did not occur during the first 30-day postoperative period.…”
Section: Discussioncontrasting
confidence: 66%
“…Unfortunately, literature has a lack of studies focusing on the effect of surgeon and center volume on LRS outcomes. However, we could expect better surgical outcomes in high-volume vs. low-volume centers, as have been previously reported for cytoreductive nephrectomy [ 16 ]. It is also worth considering the high variability among series in terms of complication reports.…”
Section: Discussionmentioning
confidence: 59%
“…On the recently published REMARCC data registry, the overall complication rate for CN was 30%, with only 6% being reported as major complications (grade 3-5 Clavien-Dindo). Less than 12% of the patients were readmitted within 30 d of surgery [7].…”
Section: Discussionmentioning
confidence: 99%
“…A retrospective review of patients diagnosed with mRCC was abstracted from the Registry for Metastatic RCC (REMARCC) database. The REMARCC collected data on patients who underwent CN between 2005 and 2019 from 14 North American and European institutions [7]. Institutional Board approval was obtained at all participating institutions when required.…”
Section: Patient Populationmentioning
confidence: 99%
See 1 more Smart Citation